A study on patterns of physical activity among medical interns in a teaching Hospital in Secunderabad, Telangana - Moluguri, Himabindu; Pulla, Anupama; Thomas, Vimala; Padmavathi, Y. (International Journal Of Community Medicine And Public Health, 2020)
Background: Regular physical activity has been regarded as an important component of healthy life style. Physical inactivity is an important risk factor for the development of many non-communicable diseases like hypertension, obesity, diabetes, coronary artery disease etc. Methods: A cross-sectional study was conducted among 300 medical interns to determine the patterns of physical activity and to assess the motivating factors and barriers for physical activity. A pre designed semistructured questionnaire was used for data collection. Data was entered into MS excel sheet and analyzed by using Epi Info.7.1.3. Version. Results: In the study about 13% of the participants had BMI≥25.00 kg/m2. About 41.7% of the total study population were engaged in some form of physical activity. Motivating factor for performing physical activity was to maintain good health as seen in 49.2% of the participants. Laziness was the major hindering factor for performing physical activity as seen in 56% of the participants. Gender and BMI had no significant relation with physical activity. Conclusions: Less than half of the study population were engaged in physical activity. Most common type of physical activity was walking/running. Most common motivating and hindering factors for performing physical activity were to maintain good health and laziness respectively. Gender and BMI had no significant relation with physical activity.